Engineering the solid oxide fuel cell electrocatalyst infiltration technique for industrial use. (7th September 2016) - Dowd, Regis P.; Lee, Shiwoo; Fan, Yueying; Gerdes, Kirk
Abstract: In this work, we explore various parameters for infiltrating La0.6 Sr0.4 CoO3-δ (LSCo) into the La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) – Ce0.8 Sm0.2 O2 (SDC) cathode of a planar solid oxide fuel cell (SOFC) using an automated solution dispensing technique for commercial deployment of infiltrated SOFCs by industry. Substrate temperature, chelating agent concentration, and surfactant type were explored to develop a 1-step infiltration process for delivering 8–10 weight percent of LSCo electrocatalyst to the cathode active layer. The results confirm increased fuel cell performance and durability by optimizing the infiltrate solution for increased transport into the cathode's microstructure. Highlights: One-step SOFC wet impregnation infiltration process is proposed. Infiltrate optimized for increased transport into porous cathode. SOFC performance and durability improve after infiltration. Low-cost automated infiltration technique favorable for commercial deployment.